PELATIHAN PEMBUATAN EVALUASI PEMBELAJARAN INTERAKTIF DENGAN WORD WALL DI SMK PEMBANGUNAN JAYA YAKAPI - Maya Nurfitriyanti; Huri Suhendri; Ul'fah Hernaeny (LPPM Universitas Bina Bangsa, 2024)
The aim of this community service implementation is to design interactive learning evaluations with wordwalls as a form of teacher innovation and creativity in teaching so that learning in the classroom can be maximized. The development of information technology is currently in the era society 5.0 so that the education system is increasingly developing, especially in learning. Existing educational development mean that teachers need to carry out developments in learning both in terms of the learning methods carried out and the learning media used. This is a challenge for teachers in utilizing technology-based media for use in learning. There are still teachers who have minimal knowledge regarding the used of technology-based learning media so they have no been able to optimize interactive learning evaluations using wordwalls. Appart from that, the main objective in implementing this community service is to assist teachers in creating innovative and interesting learning evaluations that can be used in learning. Implementation of community service by presenting material and training to teachers provided by Unindra lecturers regarding making interactive learning evaluations